"Thick or thin"? Policy and the different conceptualisations of business interaction patterns. Issue 11 (28th April 2020) - Hakansson, Hakan; Waluszewski, Alexandra
Abstract : Purpose: The prestigious policy advisor, World Economic Forum (WEF), underlines that "governments, businesses and civil society organisations" must find "new ways of tackling the systemic risks that affect us all". Paradoxically, policy's and politicians' great trust in the basic forces of the business world is accompanied with a disinterest in how they are captured in analytical approaches. The purpose of this paper is to discuss what consequences different approaches to interaction present for policy attempts to use business forces to achieve change. Design/methodology/approach: The discussion of theoretical approaches available for policy aiming to use the basic forces of business exchange for efficiency, innovation and industrial/societal renewal in specific directions is designed as follows: The authors identify two main choices of dimensions in the conceptualisation of business exchange, based on the acknowledgement of thin or thick interactions. The authors discuss how these are related to how interaction patterns appear in empirical studies of exchange. Based on the identification of conceptualisations and empirical findings, the authors discuss the ability for the public sphere to use the basic characteristics of business exchange to cope with societal challenges. Findings: Research experiences on thick interaction and its consequences, that businesses and their input and output are interdependent, systemic and promote certain development paths, are largely ignored in approaches used in policy circles. Instead, policy advisors' and policy commissioners' understanding of business interaction patterns is coloured by mainstream economies assumption of thin interaction. The content and function of the market as depicted in this tradition are within EU, the basic foundation for legal regulations and limitations of businesses interaction patterns. Simply put, actors as well as the activities and resources that they are related to are approached as independent. Research limitations/implications: This paper is focussed on the conceptual underpinnings of contemporary policy advices and commissions. This paper does not investigate deviations from these advices and commission made by policy practitioners on a local level Practical implications: The message given by theoretical approaches recognising thick interaction is that the thicker it is, the more intervening, broader and more differentiated the policy tools and measures have to be. But that also puts high demands on policy actors on all levels to have both general and specific knowledge about thick interaction patterns. However, given the big challenges the society is facing, increased speed of change and, above all, increased influence over the direction of change are needed. Social implications: WEF recognises the systemic features of the contemporary challenges to society with climate change in the foreground, and it stresses the need for finding new ways for public bodies and private businesses to cooperate to solve this. This implies the need to consider what theoretical approaches that should guide policy advice and measures. Hence, there is a need for the use of more sophisticated analytical approaches to the collective level, instead of those relying on that the interaction pattern of the business world is thin, straightforward and easy manageable. Originality/value: This paper takes a novel approach to policy advice and policy commissions through focussing on what kind of theoretical concepts and approaches that actually are available for policy advisors and policy commissioners interested in using the basic forces of business exchange to increase efficiency and innovation in the public setting in general and furthermore to solve specific problems and to create new, specific development paths. Hence, both approaches adopted and neglected by policy are considered.